Educational Values in Islamic History: A Historical Review of the Book History of the Arabs - S, Gunawan; Mubarak, Mubarak; Mukmin, Mukmin (AT-TURATS, 2025)
This research aims to examine the role of education in shaping essential values throughout the history of Arab civilization, using Philip Khuri Hitti's History of the Arabs as the main reference. A qualitative approach was used through literature review and content analysis to explore the cultural, social, political, religious and intellectual dimensions of Arab history. The findings reveal that education not only served as a means of knowledge transmission but also as an important foundation in the formation of the collective identity and social structure of Arab societies. In addition, education played an important role in maintaining the continuity cultural and religious values that remain relevant today, even influencing the process of social transformation in the modern era. So there are five forms of the value of Islamic history education itself, namely: Islamic history education that has an impact on the value of knowledge and intellectuals, the value of social education of civilization that continues to grow, the development of the value of Islamic history education in the form of religious spirituality, the political value of government in the form of Islamic history education, and the value of Islamic culture in the perspective of Islamic history education Therefore, understanding the role of education Arab history is an important basis for designing an education system that is adaptive to socio-cultural dynamics, historically contextual, and rooted in the values that have shaped the character of society. This research provides a conceptual contribution to the development of a holistic and sustainable education system. Penelitian ini bertujuan untuk mengkaji peran pendidikan dalam membentuk nilai-nilai esensial sepanjang sejarah peradaban Arab, dengan menggunakan buku History of the Arabs karya Philip Khuri Hitti sebagai referensi utama. Pendekatan kualitatif digunakan melalui tinjauan literatur dan analisis isi untuk mengeksplorasi dimensi budaya, sosial, politik, agama, dan intelektual dari sejarah Arab. Temuan penelitian mengungkapkan bahwa pendidikan tidak hanya berfungsi sebagai sarana transmisi pengetahuan, tetapi juga sebagai fondasi penting dalam pembentukan identitas kolektif dan struktur sosial masyarakat Arab. Selain itu, pendidikan berperan penting dalam menjaga kesinambungan nilai-nilai budaya dan agama yang tetap relevan hingga saat ini, bahkan mempengaruhi proses transformasi sosial di era modern. Jadi, ada lima bentuk nilai dari pendidikan sejarah Islam itu sendiri, yaitu: Pendidikan sejarah Islam yang berdampak pada nilai pengetahuan dan intelektual, nilai pendidikan sosial peradaban yang terus berkembang, pengembangan nilai pendidikan sejarah Islam dalam bentuk spiritualitas keagamaan, nilai politik pemerintahan dalam bentuk pendidikan sejarah Islam, dan nilai kebudayaan Islam dalam perspektif pendidikan sejarah Islam Oleh karena itu, pemahaman terhadap peran pendidikan sejarah Islam menjadi dasar penting untuk mendesain sebuah sistem pendidikan yang adaptif terhadap dinamika sosio-kultural, kontekstual secara historis, dan berakar pada nilai-nilai yang telah membentuk karakter masyarakat. Penelitian ini memberikan kontribusi konseptual bagi pengembangan sistem pendidikan yang holistik dan berkelanjutan.